DOMESTIC COMMUNAL WASTEWATER TREATMENT PLANT EVALUATION IN SINDANGRASA, BOGOR, INDONESIA - Purnomosutji Dyah Prinajati (Journal of Community Based Environmental Engineering and Management, 2020)
The communal domestic wastewater treatment plant functions to collect and treat domestic wastewater at the source location according to the communal scale treatment capacity. The communal Wastewater Treatment Plant (WWTP) in RT (neighborhood association) 01 / RW (citizen association) 09 Sindangrasa was built in 2016 using the Anaerobic Baffled Reactor (ABR) system. This study aims to evaluate the Communal WWTP by analyzing the quality of wastewater compared to PerMenLH No. 68 of 2016, calculates the processing efficiency and analyzes the water quality of the community wells around the Communal WWTP compared to regulation of PerMenKes No.416/MENKES/PER/IX/1990. Data collection techniques using the Slovin technique in the pre-research stage, direct sampling on location and testing in an accredited laboratory. The results showed the quality of wastewater exceeds the quality standard for BOD, TSS and Total Coliform parameters, the quality of residents' well water exceeds the quality standard for parameters pH, Cr VI and Total Coliform. Communal WWTPs in RT 01/ RW 09 Sindangrasa have not been efficient in treating residents' domestic wastewater. The management of Communal WWTPs needs to be improved so that the effluent quality and processing efficiency values ​​meet the specified regulatory standards.